Origins of Cyberjournalism - Navarro Zamora, Lizy (2011)
In the development of this research we look for the origins of Cyberjournalism which had its first exhibition in Electronic Journalism. These origins formed the basis of what is today known as cybermedia, with language and elements for the construction of these spaces. These early examples of Electronic Journalism (videotexts, teletexts, newspapers by fax, audiotex, diskette, CD-ROM, online newspapers) laid the groundwork for cyberjournalist’s formation which build emerging spaces and specific languages. It is important to emphasize the development of Electronic Journalism had its processes in European countries. Latin Americans did not know the way to practice this type of journalism.